Artificial Intelligence Technology for Restoration and Preservation of Cultural Heritage - Mshvidobadze, Tinatin (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2023)
This work explores various cultural heritage monuments situated in the Imereti region. It presents several projects that have utilized artificial intelligence and robotics technology, showcasing advancements in cultural heritage preservation. The application of these technologies in the projects described will be crucial for facilitating the restoration of cultural heritage monuments in the Imereti region. As technology continues to evolve and experts in the field become more proficient in its application, there is optimism that further advancements in the preservation and digitization of cultural heritage will ensue. The existence of digital cultural heritage will contribute significantly to recording history and enriching cultural vitality.